1956
DOI: 10.1021/jf60061a003
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues, Residual Properties of the Systemic Insecticide O,O-Dimethyl 1-Carbomethoxy-1-propen-2-yl Phosphate

Abstract: This investigation was supported in part by research grants from the Shell Development Co. and the Division of Biology and Medicine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1957
1957
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 4 publications
(8 reference statements)
1
31
0
Order By: Relevance
“…Methods have also been deseribed for tetraehlorvinphos alone (F AHEY et al 1969, BEBOZA 1966 and include Harne-photometrie deteetion (SHEBMAN and HERRICK 1971 (22a) trans-crotonate structure (22b) Mevinphos (22) In referring to the isomers it is preferable to name them as the E or Z isomers or as cis-crotonate or trans-crotonate. This is particularly desirable with these compounds since the first configurations that were assigned (CASIDA et al 1956, SPENCER et al 1958 were opposite to those above (22a and b) which are now considered to be correct (STU.ES et al 1961, STOTHERS and SPENCER 1961, FUKUTO et al 1961. In addition, the convention used by the earlier workers was different so that they assigned the wrong structure to the isomers but used the same names (cis-or trans-) for the respective isomers as those given by STU.…”
Section: F) Methods For Residue Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Methods have also been deseribed for tetraehlorvinphos alone (F AHEY et al 1969, BEBOZA 1966 and include Harne-photometrie deteetion (SHEBMAN and HERRICK 1971 (22a) trans-crotonate structure (22b) Mevinphos (22) In referring to the isomers it is preferable to name them as the E or Z isomers or as cis-crotonate or trans-crotonate. This is particularly desirable with these compounds since the first configurations that were assigned (CASIDA et al 1956, SPENCER et al 1958 were opposite to those above (22a and b) which are now considered to be correct (STU.ES et al 1961, STOTHERS and SPENCER 1961, FUKUTO et al 1961. In addition, the convention used by the earlier workers was different so that they assigned the wrong structure to the isomers but used the same names (cis-or trans-) for the respective isomers as those given by STU.…”
Section: F) Methods For Residue Analysismentioning
confidence: 99%
“…It was proposed that the significant reduction in residues was a function of the volatility of the compound. The first study of the metabolism of the compound on foliage was reported by CASIDA et al (1956) a Chemical name: dimethyl 2-methoxycarbonyl-l-methylvinyl p'hosphate (IUPAC) or l-carbomethoxy-l-propen-2-yl dimethyl phosphate, or methyl 3-(dimethylphosphoryloxy) but-2-enoate, or methyl 3-(dimethoxyphosphinyloxy) crotonate.…”
Section: A) Degradation Following Direct Application To the Plantmentioning
confidence: 99%
See 3 more Smart Citations